Acute pancreatitis after nitrous oxide abuse: A case report - Shanshan Chen; Linjie Guo; Yufang Wang (JGH Open, 2023)
Abstract The recreational use of nitrous oxide (N2O) is sharply increasing among young adults. N2O abuse can cause serious complications. However, the association between acute pancreatitis and N2O is rarely reported. Here we report a case of a young and previously healthy female with widespread cutaneous lesions, neurologic symptoms, and abdominal pain. Acute pancreatitis was the patient's primary diagnosis when she was admitted to the gastroenterology unit. We added the diagnosis of N2O intoxication after an additional inquiry into the patient's personal history revealed that she had abused N2O for 1 month. With the application of mecobalamin and other symptomatic treatments, the symptoms and laboratory indexes improved gradually. In this case, we highlight that acute pancreatitis may be a rare complication induced by N2O.